Adsorption of Metalaxyl and Glyphosate on Six Erbilian Agricultural Soils - M. SHAREEF, KAFIA; I. HAMADAMIN., SHIREEN (Asian Journal of Chemistry, 2010)
A study was conducted to determine the differences in the adsorption behaviour of two non-ionic pesticides, metalaxyl [N-(2,6-dimethyl phenyl)- N-(methoxyacetyl)] and glyphosate [N-phosphonomethyl-glycine] on six agricultural soil samples from Erbil governorate. Data from batch equilibrium method revealed that the adsorption of metalaxyl and glyphosate on the selected soil samples followed the first order rate law. Glyphosate exhibited the faster rate of accumulation with 76.53 % adsorption on the soil solid matrix after 0.5 h as compared to that for metalaxyl 66.06 %. Linear, Freundlich and Langmuir models were used to describe the adsorption of both pesticides. Values of distribution coefficient (Kd) indicated moderate to strong adsorption of metalaxyl (mean calculated Kd: 5.963 mL g-1) and very strong adsorption of glyphosate (mean calculated Kd: 703.716 mL g-1) and consequently there is no considerable risk of ground water contamination. Wide variation in adsorption affinities of the soils to both pesticides was observed, Kd values for metalaxyl varied between 2.93 and 9.97 mL g-1 and for glyphosate between 5.16 and 456.34 mL g-1. A linear correlation was found between the values of adsorption coefficients of both pesticides and soil organic carbon (R2: 0.61 and 0.69 for metalaxyl and glyphosate, respectively).